Salient features of customer engagement, visual presentation and copywriting for effective social media marketing: an exploratory perspective / Nooraini Mohamad Sheriff, Aisya Syahira Zulkifli and Wan Nur Shahira Wan Othman - Mohamad Sheriff, Nooraini; Zulkifli, Aisya Syahira; Wan Othman, Wan Nur Shahira (Universiti Teknologi MARA, Negeri Sembilan, 2018)
As internet-based marketing utilizes channels of social media to interact and attract prospective customers to make online purchase for apparels there is a need to ascertain the extent to which salient features of social media such as customer engagement, attractive visual presentation and copywriting that are capable of driving such purchase. A total of 128 usable questionnaires were included in this study. Distribution of online questionnaires was assisted where the online questionnaire link in Google document was emailed to the company’s sales team who in turn blasted the online questionnaire via email to all of their online customers in their data base. A positive significant (0.01) high correlation of .709 for customer engagement and .711 were obtained for visual presentation with online purchase for apparels. In addition, a positive significant (0.01) modest correlation of .653was secured for copywriting and online purchase of apparels. The study affirms that online firms using social media marketing must ensure they engage their online customers through discussions, reviews, contest and comments to understand them better and to build relationship between their brand and customer’s which has a positive impact on sales. Social media marketing too needs an exemplary visual presentation to explain abstract concepts and facilitates retention of information and maintain audience interest which ultimately has a positive impact on sale. Consequently, copywriting too performs an important role of convincing people about a product by transforming product features into benefits to convince readers into making a purchase.